Evaluating a vocational training programme for women refugees at the Zaatari camp in Jordan: women empowerment: a journey and not an output. Issue 3 (2nd July 2016) - Jabbar, Sinaria Abdel; Zaza, Haidar Ibrahim
Abstract: This study aims at evaluating a vocational training programme entitled 'Women and Girls Oasis' at the Zaatari Refugee Camp in the city of Mafraq, Jordan. The research study was undertaken in 2014/2015, and highlights the impact of such vocational training programmes on the well-being of Syrian women refugees. The results show that 'Women and Girls Oasis' Programme enhanced women's confidence and self-esteem, improved their occupational business, and entrepreneurship skills, helped them generate income to build a better life for their shattered families; and gave them hope and opportunities after experiencing war firsthand. The study reveals that in a refugee community, patterns are deconstructed and gender roles may be changed; this gender equality and women empowerment are seen as perquisites for sustainable development and achieving the millennium development goal. The study offers recommendations for UN Women, UNHCR and similar NGO's concerned with the well-being of refugees in Jordan and neighbouring countries.